The Stepford wives [videorecording (DVD)] - Rudin, Scott, 1958-; Oz, Frank; Rudnick, Paul; Kidman, Nicole, 1967-; Broderick, Matthew, 1962-; Midler, Bette; Walken, Christopher, 1943-; Bart, Roger; Lovitz, Jon; Hill, Faith, 1967-; Close, Glenn, 1947-; Levin, Ira, 1929-2007 (Paramount, 2017)
After moving with her husband and children to the well-manicured community of Stepford, Connecticut, former New York television executive Joanna Eberhart is beginning to realize that Stepford is more than just the "perfect" place to live ... it's a little too perfect. All the wives in town are models who cater to their husband's every desire. What is going on behind the closed doors of the Stepford Men's Association and the Stepford Day Spa? Can Joanna figure out the problem before it's too late?